The Evolution of the Classic Russian Novel of the XIX Century: Background to the Problem Statement - A. Kukuyeva, Asiyat; G. Kadimov, Ruslan; Sh. Chamsedinova, Gulnara; A. Emirova, Leyla; L. Mugumova, Anna; N. Magomedgadzhieva, Patimat (International Journal of Psychosocial Rehabilitation, 2020)
Scientific value: The article presents an independent view on the development of the classic Russian novel of the XIX century with due consideration of peculiarities of the creative method and development trends; the authors also analyzed the forms of expression of the aesthetic ideal in classic Russian literature. The scientific value lies in the fact that modern study of the Russian classics in the context of Eurasian ideas gives the formation of a new vision of social, spiritual, and cultural processes taking place in the life of modern Russian society; such study helps to identify the most optimal ways of sociocultural development of multicultural, multi-religious Russian society in modern conditions as well. The topical continuity of the presented study is primarily determined by the call for an interdisciplinary approach to the consideration of classic Russian literature of the XIX century in the context of world fine literature and art. Novelty: Due to the ongoing processes of globalization, the current evaluation and interpretation system of the creative and aesthetic perception of reality is changing. The presented article featured an attempt to describe the aesthetics of the classic Russian novel of the 19th century in the context of the Eurasian cultural and historical paradigm with reference to the universal aesthetic ideals and meanings achieved by global culture. The purpose of this article was to form a new methodological model of scientific understanding of cultural and historical’storylines’, clarifying the most important issues of the Eurasian ethnic identity of Russian culture and, respectively, Russian literature. The problem of the aesthetics of the Russian XIX century novel in the selected perspective has not yet become the subject of a special study. The article substantiated the relevance of the study of Russian classical heritage and types of literary relations peculiar to Pushkin, Turgenev, Dostoevsky, and Chekhov, which is determined, first of all, by the contemporary trend for an interdisciplinary examination of works of Russian classics. Methodology: the case study was represented by comparative-historical, cultural, and typological methods of research, allowing a comprehensive review of the development of Russian nineteenth-century literature. The Russian novel of this period was first considered in the context of the Eurasian literary community, taking into account the methodology of the concept of Eurasianism set out in the works of Nikolai Trubetzkoy, D. S. Mirsky, and Valentin Nedzvetsky on the stages of development of the Russian social-universal novel. Results: analyzing the features of the creative method of Russian writers, the revealed conceptual forms of expressing the aesthetic ideal of nineteenth-century Russian literature such as ‘prophecy’,’superfluous man’, ‘Russian wanderer’, and’symphonic personality’ were defined as unique Eurasian human characteristics and qualities. Conclusion: The article reveals the features of the creative method, type, and genre as the immediate reality of the creative thinking of Russian classics. While studying the evolution of the Russian novel from Pushkin to Chekhov, the artistic nature of the literary process in its continuity and new ascending stages of development was also reviewed (Russian novel of ordeal, the invariable form of Russian classic novel, social-universal novel). The dialogue of cultures and the renewal of traditions, the properties of a soteriological type of consciousness, a parity principle, and the spiritual and moral dominants were established as the types of literary relations and the peculiarity of the Russian literary character typical for the studied period; the’model’ of a man in the XIX century novel was attributed to the concept of’symphonic personality’, which the adherents of the Eurasian movement had comprehensively developed in their research.